Sand Distribution Controlled by Paleogeomorphology in Marine–Continental Rift Basin - Bochuan Geng; Peidong Su; Shilin Wang (Journal of Marine Science and Engineering)
The analysis of sand distribution in a marine–continental rift basin is of practical value for hydrocarbon prediction. The primary objective of this study is to investigate the correlation between Paleoproterozoic sand development and paleomorphology in the Nanpu sag, and to focus on identifying the key factors controlling sand deposition in the marine–continental rift basin. Correspondence between the development of the Paleoproterozoic sand in the Nanpu sag and the paleogeomorphology shows that the gully limited the deposition of the sand into the lake. The differentiation and aggregation of the sand in the lake basin were influenced by two kinds of slope break zones (the syn-sedimentary fracture tectonic slope break zone and the paleo-topographic flexural depositional slope break zone). Due to tectonic movements in the marine–continental rift basin, as well as provenance supply and weather during chasmic stages, the impact of valley and syndeposit slope break zone on sand development varies. In areas where allocation is better as valley–syndeposit slope break zone, basal slope and its vicinity usually are favorable for delta (braided channel) and fan delta sand development, which extend basinward through hydraulic transport. Meanwhile, under the influence of syntectonic and gravitational disequilibrium, gravity flow sand can be seen sporadically distributed in the deep end of fan fronts. This study is of great significance for oil and gas exploration in the Bohai Bay Basin region and contributes to a better understanding of depositional processes in similar marine–continental rift basins around the globe.